2012
DOI: 10.1038/mt.2012.107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus Replication by Intracellular Delivery of Multiple siRNAs by Nanosomes

Abstract: Sustained antiviral responses of chronic hepatitis C virus (HCV) infection have improved recently by the use of direct-acting antiviral agents along with interferon (IFN)-α and ribavirin. However, the emergence of drug-resistant variants is expected to be a major problem. We describe here a novel combinatorial small interfering RNA (siRNA) nanosome-based antiviral approach to clear HCV infection. Multiple siRNAs targeted to the highly conserved 5'-untranslated region (UTR) of the HCV genome were synthesized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 49 publications
2
62
0
Order By: Relevance
“…Additionally, various human or animal HCC cell lines are used to study comparative viability, apoptosis, and toxicity in response to test substances [24]. Typically, Hep 3B, Hep G2, Huh 7.5 and SK-Hep1 in human HCC cell lines and N1S1 and McA-RH7777 in rat HCC cell lines are commonly used in HCC models [25][26][27][28][29][30].…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, various human or animal HCC cell lines are used to study comparative viability, apoptosis, and toxicity in response to test substances [24]. Typically, Hep 3B, Hep G2, Huh 7.5 and SK-Hep1 in human HCC cell lines and N1S1 and McA-RH7777 in rat HCC cell lines are commonly used in HCC models [25][26][27][28][29][30].…”
Section: Cell Linesmentioning
confidence: 99%
“…[27] used HCC models with Hep G2 cell lines in their study that demonstrated and characterized the inhibition of both tumor progression, and proliferation of liver cancer in vitro and in vivo. Chandra et al [28] used Huh 7.5 cell lines to design xenograft mouse models. They evaluated the inhibition of hepatitis C virus (HCV) replication by small interfering RNA (siRNA) encapsulated into lipid nanoparticles (nanosomes).…”
Section: Subcutaneous Xenograft and Orthotopic Animal Modelsmentioning
confidence: 99%
“…In recent years, siRNA-mediated gene silencing has been extensively employed to study different RNA viruses, especially HCV [10][11][12]. HCV often causes chronic infections and, therefore, a consistent presence of effective doses of siRNA would be DOI: 10.1159/000492220 obligatory for a sustained virological response (SVR), which is feasible either by frequent deliveries of exogenous siRNA or in vivo expression of shRNA [13,14]. However, repetitive administration of exogenous siRNA may not be feasible in the clinical setting; therefore, approaches for in vivo expression of shRNAs have been evaluated [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using both in vitro and in vivo models of HCV infection, showed that repeated treatments with two siRNAs were better than a single siRNA treatment at minimizing the development of escape mutants, resulting in a rapid inhibition of viral replication. 11,12 Moreover, targeting various HTAs would be advantageous by controlling different steps of viral infection, from viral entry to cell re-infection. 6,13 Finally, previous studies have demonstrated that, in contrast to the siRNA technology, the overexpression of exogenously introduced shRNA competes with that of endogenous miRNA and thus leads to the saturation of the endogenous miRNA pathway, resulting in serious toxicity in the mouse liver and, in some instances, death.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in accordance with a study published by Sokolova et al showing that complexation of PEI with calcium phosphate particles improves siRNA delivery. 34 As combining different siRNAs has been shown to increase antiviral efficacy, 11 we prepared nanoparticles coated with two different siRNAs. HTAs constitute a promising strategy to treat HCV infection with low viral resistance to treatment.…”
mentioning
confidence: 99%